A Socialised Medical Service (London : The Socialist Medical Association, 1933)
1933 1933 1930s 21 pages for treatment or the needs of the district. This is most undesirable, and it is definitely in the public interest that voluntary hospitals should be registered or licensed just as Nursing Homes, Public Houses, and Theatres are. In some ways it is even more necessary, as the good work carried out in most voluntary hospitals may induce patients to put their trust in Institutions that are not worthy of it. Therefore, legislation should be passed to ensure that all voluntary hospitals, whether run for profit or not, should be registered and licensed by the Ministry of Health, and that no new ones should be founded unless special need for them can be demonstrated to the Ministry. The next step in the development of a national hospital system will be the repeal of clause 16 of the Local Government Act, which insists on the Municipal Hospitals exacting payment for treatment received if the patient or those responsible for his support are capable of making it. This is a particularly odious clause in the Act, for it is usually at the time that the breadwinner is sick in hospital that a family is in the greater need of financial support. The repeal of this clause will make the Municipal Hospitals free to all who need their help, and if their efficiency is insisted on by an active Ministry of Health, they will be used by an increasing number of the population. The result will almost certainly be that the present financial difficulties of the voluntary hospitals will be increased. Those who are responsible for their management and have the good of the community at heart will see the need for a unified hospital system, and will desire increasing co-operation with the Municipal Hospitals and will be willing, it is hoped, to permit the local Public Health Committee to take over the management of their hospitals, so that they may be administered as part of the Municipal system. It will be desirable to grant to the present Governors of voluntary hospitals thus taken over one-third of the seats during their lives on the Board of Management of such hospitals. 4. — PUBLIC HEALTH SERVICES Pending the development of the general State Service described above, much of the work of the present Public Health Departments can be usefully extended. Many of these services, which now exist only in an embryo form, will be equally useful and necessary when the State Service is fully developed. The necessary legislation should immediately be passed to enforce upon every Local Health Authority through its Maternity and Child Welfare Committee the duty of providing an efficient and complete Maternity Service. A sufficiency of ante-natal and post-natal clinics staffed by doctors with special knowledge and experience must be developed, and health visitors must be employed to work in conjunction with these clinics. It must be the business of the local authority to ensure that an adequate 19 292/847/1/1